ESTRO-ACROP recommendations on the clinical implementation of hybrid MR-linac systems in radiation oncology. (June 2021) - Corradini, Stefanie; Alongi, Filippo; Andratschke, Nicolaus; Azria, David; Bohoudi, Omar; Boldrini, Luca; Bruynzeel, Anna; Hörner-Rieber, Juliane; Jürgenliemk-Schulz, Ina; Lagerwaard, Frank; McNair, Helen; Raaymakers, Bas; et al.
Highlights: Hybrid MR-linac systems are a novel innovative application in radiation oncology. This recommendation provides guidance in the implementation phase of these systems. The recommendations discuss specific challenges in oMRgRT. Preparations prior to go live, MRI safety and specific training, adequate patient selection. Online adaptive treatment planning workflows and treatment delivery. Abstract: Online magnetic resonance-guided radiotherapy (oMRgRT) represents one of the most innovative applications of current image-guided radiation therapy (IGRT). The revolutionary concept of oMRgRT systems is the ability to acquire MR images for adaptive treatment planning and also online imaging during treatment delivery. The daily adaptive planning strategies allow to improve targeting accuracy while avoiding critical structures. This ESTRO-ACROP recommendation aims to provide an overview of available systems and guidance for best practice in the implementation phase of hybrid MR-linac systems. Unlike the implementation of other radiotherapy techniques, oMRgRT adds the MR environment to the daily practice of radiotherapy, which might be a new experience for many centers. New issues and challenges that need to be thoroughly explored before starting clinical treatments will be highlighted.